Soil CO2 Degassing Path along Volcano-Tectonic Structures in the Pico-Faial-São Jorge Islands (Azores Archipelago, Portugal) - Viveiros, Fátima; Marcos, Márcio; Faria, Carlos; Gaspar, João L.; Ferreira, Teresa; Silva, Catarina (Frontiers in Earth Science, 2017)
The Azores archipelago is composed of nine volcanic islands located at the triple junction between the North American, Eurasian and Nubian plates. Nowadays the volcanic activity in the archipelago is characterized by the presence of secondary manifestations of volcanism, such as hydrothermal fumaroles, thermal and cold CO2-rich springs as well as soil diffuse degassing areas, and low magnitude seismicity. Soil CO2 degassing (concentration and flux) surveys have been performed at Pico, Faial and São Jorge islands to identify possible diffuse degassing structures. Since the settlement of the Azores in the 15th Century these three islands were affected by seven onshore volcanic eruptions and at least six destructive earthquakes. These islands are crossed by numerous active tectonic structures with dominant WNW-ESE direction, and less abundant conjugate NNW-SSE trending faults. A total of 2855 soil CO2 concentration measurements have been carried out with values varying from 0 to 20.7 vol.%. Soil CO2 flux measurements, using the accumulation chamber method, have also been performed at Pico and Faial islands in the summer of 2011 and values varied from absence of CO2 to 339 g m-2 d-1. The highest CO2 emissions were recorded at Faial Island and were associated with the Pedro Miguel graben faults, which seem to control the CO2 diffuse degassing and were interpreted as the pathways for the CO2 ascending from deep reservoirs to the surface. At São Jorge Island, four main degassing zones have been identified at the intersection of faults or associated to WNW-ESE tectonic structures. Four diffuse degassing structures were identified at Pico Island essentially where different faults intersect. Pico geomorphology is dominated by a 2351 m high central volcano that presents several steam emissions at its summit. These emissions are located along a NW-SE fault and the highest measured soil CO2 concentration reached 7.6 vol.% with a maximum temperature of 77 ºC. The diffuse degassing maps show that anomalous CO2 degassing areas are controlled essentially by the tectonic structures and the lithology of the sites since the youngest volcanic systems are characterized by very low CO2 emissions.